Stearic acid methyl ester affords neuroprotection and improves functional outcomes after cardiac arrest. (August 2020) - Chen, Po-Yi; Wu, Celeste Yin-Chieh; Clemons, Garrett A.; Citadin, Cristiane T.; Couto e Silva, Alexandre; Possoit, Harlee E.; Azizbayeva, Rinata; Forren, Nathan E.; Liu, Chin-Hung; Rao, K.N. Shashanka; Krzywanski, David M.; Lee, Reggie Hui-Chao; et al.
Abstract: Cardiac arrest causes neuronal damage and functional impairments that can result in learning/memory dysfunction after ischemia. We previously identified a saturated fatty acid (stearic acid methyl ester, SAME) that was released from the superior cervical ganglion (sympathetic ganglion). The function of stearic acid methyl ester is currently unknown. Here, we show that SAME can inhibit the detrimental effects of global cerebral ischemia (i.e. cardiac arrest). Treatment with SAME in the presence of asphyxial cardiac arrest (ACA) revived learning and working memory deficits. Similarly, SAME-treated hippocampal slices after oxygen-glucose deprivation inhibited neuronal cell death. Moreover, SAME afforded neuroprotection against ACA in the CA1 region of the hippocampus, reduced ionized calcium-binding adapter molecule 1 expression and inflammatory cytokines/chemokines, with restoration in mitochondria respiration. Altogether, we describe a unique and uncharted role of saturated fatty acids in the brain that may have important implications against cerebral ischemia.